Hierarchies of the Human - Luca Scuccimarra (University of Bologna, 2021)
This monographic section has as its purpose a reflection on the theme of the human, its hierarchies and the debate around them that in an era of «walled states» and «crimes of solidarity» it is necessary to critically rethink, reanalyze and discuss to rethink the conditions and prerogatives of the human.